Effects of Crumb Rubber Size and Concentration on Performance of Porous Asphalt Mixtures - Altan Cetin (International Journal of Polymer Science, 2013)
The purpose of this study is to investigate the effect of size distribution and concentration of crumb rubber on the performance characteristics of porous asphalt mixture. The recycling of scrap tires in asphalt pavements appears as an important alternative providing a large-scale market. The characteristics of bitumen are very important with regard to service life of porous asphalt pavement. The experimental study consists of two main steps. Firstly, the mixture design was performed to determine the optimum bitumen content. In the latter step, the mixtures were modified by dry process using crumb rubber in three different grain size distributions of #4~#20, #20~#200, and #4~#200 and rubber content of 10%, 15%, and 20% as weight of optimum bitumen. The permeability, Cantabro abrasion loss, indirect tensile strength, moisture susceptibility, and resilient modulus tests were carried out on the specimens. Test results show that #20~#200 sized rubber particles reduced air voids and coefficient of permeability, while they increased the Cantabro abrasion loss. In general, increasing the crumb rubber size and content decreased the performance characteristics of the porous asphalt mixtures.